The genus Coelichneumon Thomson in Japan (Hymenoptera, Ichneumonidae, Ichneumoninae) - Riedel, Matthias; Watanabe, Kyohei (Zootaxa, 2021)
In this taxonomic study, 29 species of the genus Coelichneumon Thomson, 1893 found in Japan are described in detail. For some species, other East Palaearctic material is also mentioned. Five of the species are new to science: Coelichneumon caerulogaster nov. sp. (from Hokkaido and Honshu), C. carinator nov. sp. (from Honshu; also Russia and Korea), C. cyanator nov. sp. (from Honshu), C. terebrator nov. sp. (from Honshu) and C. uchidai nov. sp. (from Honshu). Four species are newly reported from Japan: C. clypeatus (Uchida, 1955), C. decemguttatus Uchida, 1932, C. maritimensis Heinrich, 1980 and C. nobilis (Wesmael, 1857). C. femoralis Uchida, 1927 is newly recorded from Far East Russia and C. rufibasalis (Uchida, 1927) from China and Mongolia. C. birmanicus Heinrich, 1966 is newly synonymized under Ichneumon bivittatus Matsumura, 1912. C. coxalis Uchida, 1926 is newly synonymized under Ichneumon sinister Wesmael, 1848, and Ichneumon flavitarsis Smith, 1874 is newly synonymized under Ichneumon deliratorius Linnaeus, 1758. The female of C. rufibasalis (Uchida, 1927) and the male of C. maritimensis Heinrich, 1980 are described for the first time. For C. flavitarsis sensu Lee et al. non Smith, a new name, C. flavitarsator, is established and a lectotype designated. The genus Aglaojoppa Cameron, 1901 is newly synonymized under Coelichneumon. Hence, A. centummaculata (Christ, 1791) is transferred to Coelichneumon (rev. stat.). The specific names of A. rufofemoratus Cameron, 1903 and A. victoriae Heinrich, 1968 are preoccupied in Coelichneumon and two replacement names are proposed, Coelichneumon cameroni nom. nov. for the former and C. paravictoriae nom. nov. for the latter species.